Eco-friendly corrosion inhibition study of Croton extracts (Euphorbiaceae) for mild steel in HCl 1.0 M: Experimental and theoretical studies - Carlos Andrés Coy-Barrera; Lili Dahiana Becerra; Sergio Alejandro Torres-Cortés; Vicky Carolina Gonzalez (Results in Chemistry, 2025)
The present study evaluated the corrosion inhibition properties of extracts from Croton species on mild steel sheets in a 1.0 M HCl acidic medium. Electrochemical techniques, including potentiodynamic polarization and electrochemical impedance spectroscopy, were employed to investigate electron transfer mechanisms and inhibition behaviors. One of the extracts from Croton bogotanus exhibited a corrosion inhibition percentage of 67.5 % at 100 ppm, possibly due to its high content of quercetin and isorhamnetin and its possible relation with antioxidant activity and phenolic content. Scanning electron microscopy was used to examine morphological changes on the metallic substrates. It is essential to mention that no studies have been published on their corrosion-inhibiting properties. Additionally, corrosion rates and chemical interactions between the extracts and the metallic surface were analyzed using weight loss tests and Freundlich and Langmuir isotherm models. Analytical tools, including HPLC-MS, confirmed that the extracts are rich in isoflavones, particularly quercetin, isorhamnetin, and 5-hydroxy-7-methoxy-flavone. FT-IR spectra were recorded and analyzed to review the similarities in functional groups among the extracts. These results suggest the potential of extracts as environmentally friendly corrosion inhibitors, that provide sustainable solutions for corrosion mitigation in industrial environments. Finally, this study becomes a model of reasonable methodology that starts from species with significant flavonoid-like compounds, which reduces costs in the experimental part because the need to extract and purify natural compounds from techniques such as FTIR and HPLC-MS with the support of DFT calculations can obtain complete and reliable information.